DEGISN OF A CHARGING SYSTEM USING AN ALTERNATOR TO SUPPORT THE PERFORMANCE OF THE REGENERATIVE BREAK SISTEM IN ELECTRIC VEHICLE - Ma’sum, M. Arif; Wardani, Ni Wayan; Silaen, Debora Hotnauli (IJISCS (International Journal of Information System and Computer Science), 2024)
The use of electric vehicles is now supported by a braking system capable of absorbing energy wasted from the braking process, known as regenerative brake. This research aims to optimize the use of the regenerative brake system by adding an alternator as a power generator to achieve more optimal charging. The voltage magnitude in the testing of the electric motorcycle NIU GOVA 03 obtained a generation voltage of 26VDC when traveling downhill for 100 meters at a speed of 45km/h. After designing the alternator for the electric motorcycle, the generation output increased to meet the battery charging voltage specification of 74VDC, suitable for application as a power source for a battery with a capacity of 60V14.7Ah. The braking portion before using the regenerative brake system over a distance of 100 meters took 4.8 seconds, but after implementing the regenerative brake system, the time decreased to 5.1 seconds. This indicates that the regenerative brake system, coupled with the alternator, can provide an effect in the form of decelerating the electric motorcycle by 8.7%.